Parenting children with Down syndrome: Societal influences. (December 2017) - Huiracocha, Lourdes; Almeida, Carlos; Huiracocha, Karina; Arteaga, Jorge; Arteaga, Andrea; Blume, Stuart
Most studies of parenting children with Down syndrome (DS) have been conducted in industrialized countries. They suggest that sensitive communication on the part of professionals, and social support, can lead to acceptance and positive adjustments in the family. This study examined the impact of a diagnosis of DS on Ecuadorian families, in particular at how the diagnosis had been communicated and received, as well as the feelings and experiences which followed. Despite considerable progress in recent years, Ecuador is still marked by discriminatory attitudes which affect children with disabilities and their families, and by the persistence of widespread poverty. This qualitative study, conducted in Cuenca, Ecuador's third largest city, is based on a focus group discussion and four in-depth interviews with Ecuadorian parents of DS children attending a specialist center in the city. The study shows that, reflecting the effects of status differences and lack of appropriate training, professionals rarely communicate a DS diagnosis in an appropriate manner. Further, it is shown that lack of social support, and the widespread stigmatization confronting children with DS and their families, hinder development of positive and empowering adjustments that would best serve the child's and the family's interest.